Assessment of the validity and reliability of the Jenkins Sleep Scale in ankylosing spondylitis - (:unkn) unknown (WILEY, 2019)
Aim Ankylosing spondylitis (AS) affects sleep quality. Jenkins Sleep Scale (JSS) Evaluation Questionnaire is a simple and easy to understand scale. The aim of this study is to constitute validity and reliability of JSS-TR in AS patients. Methods Jenkins Sleep Scale was translated and culturally adapted by using guidelines. Clinical and demographic data of AS patients were noted. Correlations with other functional parameters such as Multidimensional Assessment of Fatigue (MAF) scale, Ankylosing Spondylitis Quality of Life (ASQoL), Pittsburgh Sleep Quality Index (PSQI) were used to assess convergent validity of JSS-TR (Turkish version). Discriminant validity was also assessed. Shapiro-Wilk test was used as a test of normality. Spearman's rank correlation coefficient (rho) was used to assess the relation. Results Sixty patients (24 female and 36 male) with mean age of 39.6 +/- 10.8 years were recruited. The JSS-TR took an average of 1.5 minutes (+/- 30 seconds) to complete. JSS-TR had the strongest correlation with PSQI scores (rho = 0.75) and moderate-strong correlations with MAF, ASQoL, and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) scores. There was insignificant correlation with non-clinical parameters. Conclusions JSS-TR is a valid, simple and feasible sleep instrument that can be easily applied to AS patients both in research and clinical settings.
Keywords: ankylosing spondylitis; Jenkins Sleep Scale; rheumatic diseases; sleep; CROSS-CULTURAL ADAPTATION; QUALITY-OF-LIFE; PSYCHOLOGICAL STATUS; DISEASE-ACTIVITY; TURKISH VERSION; QUESTIONNAIRE; PREVALENCE; INSTRUMENT; FATIGUE; DISTURBANCE